Double heart rupture after acute myocardial infarction: A case report - Ivanov, Igor; Lovrenski, Aleksandra; Dejanović, Jadranka; Petrović, Milovan; Jung, Robert; Raffay, Violetta (Vojnosanitetski pregled, 2014)
Introduction. Double heart rupture is a rare complication of acute myocardial infarction with high mortality. Case report. We presented a 67-year-old female patient with symptoms and signs of myocardial infarction, diagnosed with echocardiography, rupture of the septum, the presence of a thrombus and a small pericardial effusion. Soon after admission the patient died. Autopsy revealed tamponade and double myocardial rupture, free wall rupture and ventricular septal rupture, as a cause of death. Conclusion. This case highlights the need to evaluate patients with myocardial infarction, recurrent chest pain, echocardiographic signs of effusion and the presence of thrombus in the pericardium in terms of double rupture of the heart.
Keywords: myocardial infarction; acute disease; heart rupture; post-infarction; echocardiography